THE APOLOGY STRATEGIES IN SIMULATED CLASSROOM SITUATIONS USED BY THE FEMALE AND THE MALE STUDENTS OF THE ENGLISH DEPARTMENT OF PETRA CHRISTIAN UNIVERSITY, SURABAYA - Venny Angelina Handoko; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2015)
This thesis is the study of apology strategies and the similarities and/or the differences of the types of apology strategies used by the female and the male students. My respondents consist of 20 female and 20 male students of the English Department. This study used the theory of Ogiermann (2009). I constructed my own Discourse Completion Test (DCT) questionnaire consisting of 10 simulated classroom situations. The quantitative approach was used in this study. The finding revealed that the first three most dominant types of strategies used by the both of them were expression of regret, acceptance of responsibility and justification. The similarities and/or the differences of the three most dominant types of apology between the female and the male students were found in the percentage use of apology strategies. Expression of regret was used 52.8% by the female students and 47% by the male students. The female students used 53.3% and the male students used 46.6% in acceptance of responsibility. Justification was used 52.7% by the female and 47.3% by the male students. For that reason, the female and the male students tend to use the same types of apology strategies, although their percentages are only slightly different.